Concomitant Liposuction Reduces Complications of Vertical Medial Thigh Lift in Massive Weight Loss Patients. Issue 6 (June 2016) - Schmidt, Manfred; Pollhammer, Michael S.; Januszyk, Michael; Duscher, Dominik; Huemer, Georg M.
Abstract : Background: Medial thigh lift procedures in the massive weight loss population have been associated with significant complication rates. Liposuction-assisted medial thighplasty has recently been introduced as a technical advancement to improve outcomes. To date, no study is available directly comparing the traditional approach and this new technique. Here, the authors evaluate outcomes and complications of both techniques in a retrospective cohort study. Methods: Outcomes of 59 patients undergoing vertical medial thighplasty at the authors' institution between 2008 and 2014 were assessed retrospectively. Evaluated parameters include age, sex, body mass indices, method of weight loss, comorbidities, and complications (e.g., seroma, infection, wound dehiscence, hematoma, and surgical revision). Appropriate statistical analysis was performed. Results: There were 29 patients in the excision-only group and 30 patients in the liposuction-assisted group (all women; average age, 41.5 years). The overall complication rate was significantly reduced in the liposuction-assisted group (13 percent versus 59 percent; p < 0.001). The incidence of individual complications such as seroma formation (zero patients versus 10 patients; p < 0.001) and wound infection (one patient versus eight patients; p = 0.01) was significantly less in the liposuction-assisted group. In addition, we observed a significantly shorter hospital stay (6.0 days versus 7.8 days), reduced number of follow-up visits (2.0 versus 4.4), and reduced time to drain removal (1.8 days versus 4.1 days; p < 0.001) in the liposuction-assisted group. Conclusions: Liposuction-assisted medial thighplasty led to a significant reduction of complications and faster recovery in the massive weight loss patient population. As a consequence, the excision-only vertical thigh lift has been completely abandoned in the authors' clinical practice. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.